Response of tuberose(polianthes tuberosa L.) to organic manures and growth promoting microorganisms - Mini sankar (Department Of Pomology & Floriculture,College of Horticulture, 2008)
Tuberose is one of the most important bulbous plants, much adored for its colour, elegance and fragrance. Among the commercially cultivated flowers in India tuberose occupies a prime position due to its popularity as cut flower as well as loose flower. It has got great potential in perfume industry also owing to the presence of much valued essential oil. The flower spikes are largely used for vase decoration and bouquet preparation and loose flowers for making garlands and in floral ornaments.